A situation-specific approach to measure attention in adults with ADHD: The everyday life attention scale (ELAS). Issue 5 (3rd September 2019) - Groen, Yvonne; Fuermaier, Anselm B. M.; Tucha, Lara; Weisbrod, Matthias; Aschenbrenner, Steffen; Tucha, Oliver
ABSTRACT: This study describes the development and utility of a new self-report measure of attentional capacities of adults with Attention Deficit Hyperactivity Disorder (ADHD): the Everyday Life Attention Scale (ELAS). Different from previous attention scales, attentional capacities are rated for nine everyday situations. Study 1 investigated the factor structure, validity, and reliability of the ELAS in 1206 healthy participants. Confirmatory factor analysis supported a situation-specific approach which categorizes everyday attention into nine situation scales: Reading, Movie, Activity, Lecture, Conversation, Assignment, Cooking, Cleaning up, and Driving. Each scale was composed of ratings for sustained, focused, selective, and divided attention as well as motivation, and had good internal consistency. Most scales showed weak correlations with ADHD Symptoms, Executive Functioning, and Memory Efficacy. Study 2 further investigated the sensitivity of the ELAS in 80 adults with ADHD compared to matched healthy controls and a mixed clinical group of 56 patients diagnosed with other psychiatric disorders. Compared to healthy controls, patients with ADHD reported reduced attentional capacities with large effect sizes on all situation scales and had a substantially higher number of situations with impaired attention scores. The ELAS may become useful in the clinical evaluation of ADHD and related psychiatric disorders in adults.